2010
DOI: 10.1111/j.1556-4029.2010.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Soils at Regional and Local Levels Using Bacterial and Fungal T-RFLP Profiling*

Abstract: DNA profiling of microbial communities has been proposed as a tool for forensic comparison of soils, but its potential to discriminate between soils from similar land use and/or geographic location has been largely unexplored. We tested the ability of terminal restriction fragment length polymorphism (T-RFLP) to discriminate between soils from 10 sites within the Greater Wellington region, New Zealand, based on their bacterial and fungal DNA profiles. Significant differences in bacterial and fungal communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…Soil community metagenomic techniques such as T-RFLP (Heath and Saunders, 2006;Horswell et al, 2002;Macdonald et al, 2011;Meyers and Foran, 2008), denaturing gradient gel electrophoresis (DGGE) (Lerner et al, 2006), and amplicon length heterogeneity-polymerase chain reaction (ALH-PCR) (Moreno et al, 2006) have been evaluated for their usefulness in forensic investigations. Lerner et al (2006) concluded that DGGE was potentially useful but applied a long list of caveats to its wide adoption by forensic practitioners.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil community metagenomic techniques such as T-RFLP (Heath and Saunders, 2006;Horswell et al, 2002;Macdonald et al, 2011;Meyers and Foran, 2008), denaturing gradient gel electrophoresis (DGGE) (Lerner et al, 2006), and amplicon length heterogeneity-polymerase chain reaction (ALH-PCR) (Moreno et al, 2006) have been evaluated for their usefulness in forensic investigations. Lerner et al (2006) concluded that DGGE was potentially useful but applied a long list of caveats to its wide adoption by forensic practitioners.…”
Section: Introductionmentioning
confidence: 99%
“…Lerner et al (2006) concluded that DGGE was potentially useful but applied a long list of caveats to its wide adoption by forensic practitioners. Macdonald et al (2011) evaluated T-RFLP on soil bacterial and fungal communities as a method of discriminating among sites of similar geology. They were able to discriminate statistically among 93% of their sites, although principal component analysis revealed high similarity among sites.…”
Section: Introductionmentioning
confidence: 99%
“…This is a significant finding given the common requirement to exclude an alibi site that is located close to the crime scene. It is also potentially advantageous to forensic investigations as these methods of analysis are rapid and require a minimal amount of sample to be able to provide a reliable analytical result and can be used in combination with other independent analyses such as those discussed by Guedes et al 40 and Macdonald et al 41 .…”
Section: Resultsmentioning
confidence: 98%
“…Microbial DNA extracted from soil was provided by the Institute of Environmental Science and Research (ESR) Ltd in Porirua [18]. DNA was extracted from samples of soil using a fast prep\ soil kit (BIO 101).…”
Section: Samples and Bacterial Strainsmentioning
confidence: 99%